Cleavage of Mucin and Salivary Agglutinin by Partiallypurified Protease from Native Strain of Streptococcus Mutansan67 - Mayssaa E Abdalah (Journal of Global Pharma Technology, 2018)
Streptococcus mutansAN67 is olatecommensal species of the human oral cavity and their role as a major causative agent associated with dental plaque.S.mutansAN67 was selected as the most active isolate for protease production. Separation and purification of Streptococcusmutans AN67 proteolytic enzyme was done by 0-70% (w:v) saturated ammonium sulfate and ion-exchange chromatography on the DEAE-cellulose column. Partiallypurified protease by ion-exchange chromatography was given an activity of 24 Unit/ml, protein concentration of 0.038 mg/ml, specific activity of 631.5 Unit/mg with purification fold of 2.8and a yield of42 %. Determination of molecular weight for partially purified protease from S. mutans AN67 was elucidated by the use of gel filtration on Sepharose-6B column, which determined as 134000Da.Partially purified protease was tested for cleavage of mucin and agglutinin proteins by gel filtration chromatography on Sepharose-6B column. Partially purified protease was able to cleave mucin protein substrate into three fractions; also it’s cleaving agglutinin protein into three fractions.Keywords: Streptococcusmutans, Protease, Mucin, Agglutinin.